Dialysis Care and Dialysis Funding in Asia - Tang, Sydney C W; Yu, Xueqing; Chen, Hung Chun; Kashihara, Naoki; Park, Hyeong Cheon; Liew, Adrian; Goh, Bak Leong; Nazareth, Maria Gina C; Bunnag, Sakarn; Tan, Jackson; Lun, Virithy; Lydia, Aida; et al. (American journal of kidney diseases, 2020)
Asia is the largest and most populated continent in the world, with a high burden of kidney failure. In this Policy Forum article, we explore dialysis care and dialysis funding in 17 countries in Asia, describing conditions in both developed and developing nations across the region. In 13 of the 17 countries surveyed, diabetes is the most common cause of kidney failure. Due to great variation in gross domestic product per capita across Asian countries, disparities in the provision of kidney replacement therapy (KRT) exist both within and between countries. A number of Asian nations have satisfactory access to KRT and have comprehensive KRT registries to help inform practices, but some do not, particularly among low- and low-to-middle-income countries. Given these differences, we describe the economic status, burden of kidney failure, and cost of KRT across the different modalities to both governments and patients and how changes in health policy over time affect outcomes. Emerging trends suggest that more affluent nations and those with universal health care or access to insurance have much higher prevalent dialysis and transplantation rates, while in less affluent nations, dialysis access may be limited and when available, provided less frequently than optimal. These trends are also reflected by an association between nephrologist prevalence and individual nations' incomes and a disparity in the number of nephrologists per million population and per thousand KRT patients.